2013
DOI: 10.1109/lgrs.2012.2208261
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Madden–Julian Oscillation in the Indian Ocean From Satellite Altimetry

Abstract: The role of air-sea interaction on Madden-Julian oscillation (MJO) propagations across the tropical Indian Ocean is analyzed using integrated multimission satellite measurements of sea surface height and outgoing longwave radiation (OLR). MJO-related activity is observed in both parameters in the eastern equatorial Indian Ocean indicating a unique interaction in this region. In the eastern Indian Ocean, atmospheric conditions appear to aid in the creation of equatorial Rossby waves, while in the central and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…This is consistent with the findings of other studies in the Indian Ocean, which found satellite salinity products (e.g. Aquarius, SMOS, and SMAP) to have a comparable standard error (Grunseich & Subrahmanyam, ; Guan et al, ). SODA SSS and ORAS5 SSS were found to be the closest to Argo.…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with the findings of other studies in the Indian Ocean, which found satellite salinity products (e.g. Aquarius, SMOS, and SMAP) to have a comparable standard error (Grunseich & Subrahmanyam, ; Guan et al, ). SODA SSS and ORAS5 SSS were found to be the closest to Argo.…”
Section: Resultssupporting
confidence: 92%
“…The seasonal reversal of winds in the Somali Current region trigger an equatorial Kelvin wave response that propagate eastward across the Indian Ocean and reflect back as a downwelling Rossby wave. This Rossby wave deepens the mixed layer and thermocline, warming sea surface temperatures (SSTs), and triggering atmospheric MJO convection (Aiyyer & Molinari, ; Chen et al, ; Grunseich, Subrahmanyam, Arguez, ; Grunseich, Subrahmanyam, Murty, et al, ; Grunseich & Subrahmanyam, ; Hendon et al, ; Li et al, ; Matthews, ; Webber et al, , ). Using satellite altimetry data, Grunseich and Subrahmanyam () were able to confirm the impact Kelvin and Rossby waves have on MJO initiation, showing that satellite observations can be used to accurately monitor and predict these ISOs.…”
Section: Introductionmentioning
confidence: 99%
“…The MJO has been studied using various observations of the large‐scale characteristics of the atmosphere and ocean, mostly from satellites due to their comprehensive spatiotemporal coverage. These include outgoing longwave radiation (OLR), precipitation and wind for the atmosphere, and SST and sea surface height for the ocean [ Hendon and Salby , ; Arguez et al , ; Benedict and Randall , ; Waliser et al , ; Grunseich and Bulusu , ]. Observational studies inferring interactions between the MJO and the near‐surface ocean date back over two decades [ Krishnamurti et al , ; Kawamura , ; see reviews by Hendon , ; Duvel , ].…”
Section: Introductionmentioning
confidence: 99%
“…Such ocean feedback considerably improved MJO simulations and MJO predictability/predictive skills for some coupled ocean-atmosphere models [Flatau et al, 1997;Waliser et al, 1999;Inness et al, 2003;Fu et al, 2007Fu et al, , 2013, suggesting potential importance of the ocean in understanding and predicting the MJO.The MJO has been studied using various observations of the large-scale characteristics of the atmosphere and ocean, mostly from satellites due to their comprehensive spatiotemporal coverage. These include outgoing longwave radiation (OLR), precipitation and wind for the atmosphere, and SST and sea surface height for the ocean [Hendon and Salby, 1994;Arguez et al, 2005;Benedict and Randall, 2007;Waliser et al, 2009;Grunseich and Bulusu, 2013]. Observational studies inferring interactions between the MJO and the near-surface ocean date back over two decades [Krishnamurti et al…”
mentioning
confidence: 99%